Evaluation of human exposure to single electromagnetic pulses of arbitrary shape - Jelínek, Lukáš; Pekárek, Luděk (Central European Journal of Public Health, 2006)
Transient current density J(t) induced in the body of a person exposed to a single magnetic pulse of arbitrary shape or to a magnetic jump is filtered by a convolution integral containing in its kernel the frequency and phase dependence of the basic limit value adopted in a way similar to that used for reference values in the International Commission on Non-Ionising Radiation Protection statement. From the obtained time-dependent dimensionless impact function WJ(t) can immediately be determined whether the exposure to the analysed single event complies with the basic limit. For very slowly varying field, the integral kernel is extended to include the softened ICNIRP basic limit for frequencies lower than 4 Hz.
Keywords: Risk Assessment; vystavení vlivu životního prostředí; Humans; lidé; hodnocení rizik; Electromagnetic Fields; Environmental Exposure; elektromagnetická pole; Threshold Limit Values; prahové limitní hodnoty